Rzeczownik herzt i jego derywaty w gwarach okolic Biecza na Pogórzu .......... 257 - Karaś, Halina (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
THE NOUN HERZT AND ITS DERIVATIVES IN THE DIALECTS OF THE BIECZ AREA IN THE POGÓRZE REGIONThe article discusses the dialectal word herzt 1. ‘formerly: a man working at the front and setting the pace of work’, 2. ‘formerly: front, first place, priority’, and its derivatives: herztować, herztowo, herztownica, herztowy. The paper presents the specific dialectal meaning of the word/words, their geographic range, structure, and etymology. It also highlights the history of the word in standard Polish based on historical and contemporary dictionaries of standard Polish and etymological dictionaries. The paper is based on material collected during research into dialects of the Biecz area that was conducted in connection to the work on a dialectal dictionary of this region.